Viral Politics and Platform Power: TikTok’s Role in Shaping Electoral Discourse in Southeast Asia - Febriana, Ajeng Iva Dwi; Rahman, Sirajul (Communica : Journal of Communication, 2024)
This study examines how TikTok has transformed political campaigning and discourse in Southeast Asia, focusing on the 2022 and 2024 elections in Indonesia, Malaysia, and the Philippines. Using qualitative content analysis of TikTok content tagged with political hashtags, the research draws on platform governance theory and emotional resonance metrics to assess engagement patterns, influencer behavior, and algorithmic amplification. Findings reveal that TikTok’s short-form, emotionally resonant videos allow both official campaigns and grassroots creators to bypass traditional media gatekeeping. In Indonesia, meme-driven user content often achieved engagement rates above 60%, surpassing official campaign videos and highlighting humor and satire as dominant forms. In Malaysia, politicians such as Syed Saddiq gained more than 500,000 new followers during the 2022 campaign by employing authentic, relatable storytelling to connect with voters. In the Philippines, coordinated influencer networks generated millions of views for revisionist historical narratives, demonstrating the risks of emotionally charged disinformation. Comparative analysis shows how TikTok operates differently across Southeast Asia’s sociopolitical contexts: Indonesia illustrates the power of grassroots humor, Malaysia underscores the effectiveness of storytelling in political outreach, and the Philippines exposes vulnerabilities to disinformation through influencer coordination. Overall, the study underscores a paradox. TikTok democratizes political expression by lowering barriers for participation but simultaneously magnifies post-truth dynamics and risks marginalizing dissenting voices through algorithmic bias. To address these challenges, the study recommends strengthening algorithmic transparency and implementing targeted digital literacy programs for youth voters in Southeast Asia. These measures are vital to safeguarding democratic integrity within rapidly evolving digital spaces.